The Impact of Slipper Microstructure on Slipper-Swashplate Lubrication Interface in Axial Piston Pump - Jihai Jiang; Zebo Wang; Geqiang Li (IEEE Access, 2020)
In order to decrease the tilt and eccentric abrasion of a slipper and improve the lubrication performance of the slipper-swashplate interface in an axial piston pump, this paper proposes a comprehensive numerical simulation method to predict the lubrication performance and designs three types of slipper microstructures such as micro-chamfering, micro-filleting and micro-stepping to improve the lubrication performance. The lumped-parameter numerical pressure-flow model of the axial piston pump and the lubrication model of the slipper-swashplate interface have been developed. These models consider the pressure of slipper's center oil pool, hydrostatic lubrication, hydrodynamic lubrication, slipper microstructures, slipper's micro motion and dynamic equilibrium. The influence of slipper microstructures on the lubrication performance of the slipper-swashplate interface has been profoundly studied. Simulation results demonstrate that the slipper without a microstructure leans forward and finally touches the swashpate leading to wear-out and that all the three types of slipper microstructures improve the lubrication performance, where the effects of micro-chamfering and micro-filleting are better than the effect of the micro-stepping. With the increase of the micro-chamfering depth, the leakage decreases and the friction power loss increases, while with the increase of the micro-chamfering depth, the leakage increases and the friction power loss decreases. The experimental results are essentially consistent with the simulation results, which confirms the numerical models feasible and effective. The current work is significant for further designs and the structural optimization of the slipper-swashplate interface.